Biological Activities of Novel Thienothiazine Derivatives on Heart and Smooth Muscle Preparations of Guinea Pigs - Studenik, Christian; Lemmens-Gruber, Rosa; Heistracher, Peter (Arzneimittelforschung, 1999)
New thienothiazine derivatives which differ in their side chains on the nitrogen atom of the thienothiazine ring were investigated regarding their biological activity and compared with calcium antagonistic drugs. Isometric contraction force was measured in guinea-pig papillary muscles, aortic strips and terminal ilea. Chronotropic activity was studied in right atria of guinea pigs. MS 69 with a ethylpyridylcarbonyl side chain had the most potent negative inotropic effect on isolated papillary muscles, followed by MS 74, which has an ethylmethylpiper-azinylthiocarbonyl side chain. The negative inotropic effect could be antagonized by increasing the extracellular calcium concentration. MS 87 with an ethylpyridylcarboxamide side chain had the most potent relaxing effect on aortic strips and MS 48 with an ethylbenzylpiperazinylcarbonyl side chain was most potent on terminal ilea. Compounds with a more hydrophilic side chain had less activity. It is concluded that increasing the lipophilicity by substitution of an oxygen atom by a sulfur atom (MS 74) or addition of a pyridine ring (MS 69) results in a higher biological activity.
Keywords: Calcium antagonists; Thienothiazine derivatives, effects on aortic strips, papillary muscles, right atria, terminal ilea